Demographics of new diagnoses of leprosy in the UK over 23 years: a retrospective study of cases at the Hospital for Tropical Diseases, London. Issue 2 (28th February 2020) - McIntosh, Amy; Checkley, Anna; McBride, Angela; Walker, Steve; Lockwood, Diana
Abstract : BACKGROUND: Leprosy is rare in the UK, but migration from endemic countries results in new diagnoses annually. Early recognition, diagnosis and treatment can prevent harmful stigma and disability. METHODS: We conducted retrospective analysis from a database of new cases of leprosy seen at the Hospital for Tropical Diseases, London from 1995 to 2018. We aimed to identify typical demographics of patients presenting with leprosy and identify causes and consequences of delayed diagnosis. RESULTS: 157 cases were included. A large proportion were male (67.5%) with a median age of 34 years. Most were non-UK born and migrated in adulthood. 41.3% of cases were acquired in India, Sri Lanka or Bangladesh. Borderline tuberculoid (43.9%) was the most common type, followed by lepromatous leprosy (33.8%). The mean time between arrival in the UK and symptom onset was 5.87 years (SD 10.33). It took over 5 years for 12.8% of patients to be diagnosed. 93.6% of patients completed multidrug treatment following diagnosis. CONCLUSION: Male predominance and age at diagnosis reflects global epidemiology of leprosy. Patterns of acquisition reflect trends in UK migration from endemic countries. The typical patient presenting to the clinician is a young male who has migrated as an adult and developed symptoms in the years surrounding migration. Many patients may have developed disability before treatment commences as the time to diagnosis can be prolonged. Once diagnosed in the UK, treatment is of high quality, readily available, and effective: earlier recognition by clinicians can prevent disability and reduce the risk of transmission.